Agribisnis Kedelai Lahan Kering Untuk Mendukung Keamanan Pangan di Kecamatan Galis, Bangkalan - Wijayanti, Dian Eswin; Purnama, Mohammad Andhika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Food security is one of the development focuses of the Indonesian government. One of the important commodities in food crop commodities is soybean. The level of soybean imports in Indonesia is still very high. In the last five years, the average volume of soybeans imported by Indonesia is 6.88 million tons per year. The rate of imports must be suppressed immediately, namely by providing local soybeans. One of the soybean centers in Bangkalan Regency is Galis District which is the sub-district with the highest soybean production, but the trend of soybean production shows a decline, this indicates a problem with the soybean agribusiness system. Therefore, the purpose of this study is to analyze dryland soybean farming in Galis District with an agribusiness system approach. This study used a qualitative descriptive method, namely by analyzing dryland soybean farming with an agribusiness system approach consisting of upstream, farming, downstream subsystems, and supporting institutions. The results showed that in the upstream subsystem, the agricultural inputs used were wilis soybean seeds, TSP fertilizer, Urea, KCl, and NPK, Hopsin 50 EC insecticide, and agricultural machinery. The farming process consists of land preparation, planting, embroidery, seeding, fertilizing, and harvesting. Post-harvest handling is only done by drying and stripping the epidermis, after which it is distributed to middlemen and sellers who will later be marketed to Pasar Atom, Surabaya, and Sepuluh District, Bangkalan.